The Relationship Between Mental Health and Drugs used in Dermatology - Maria Krzyżanowska; Julia Piątkiewicz; Mateusz Sztybór; Gabriela Nowak; Marcin Kapica; Karol Momot; Mikołaj Wojtas; Karen Głogowska; Monika Maleszewska; Aleksandra Żmijewska (Kazimierz Wielki University, 2024)
INTRODUCTION: Dermatological diseases are a common clinical problem in medical practice. Various groups of medications are used in their treatment. Psychiatric disorders also present a significant challenge for modern medicine, some of them may have iatrogenic origins. This study analyzes drugs used in dermatological diseases and their impact on mental health. REVIEW METHODS: This review of the literature collects data from PubMed and Google Scholar about medications used for treating dermatological conditions and their potential impact on mental health. THE STATE OF KNOWLEDGE: Acyclovir, valacyclovir, chloroquine, hydroxychloroquine, tetracyclines, retinoids, glucocorticoids, 5-alpha-reductase inhibitors, dapsone and methotrexate are mentioned in the literature as possible, but rare causes of the onset /exacerbation of various psychiatric symptoms. Comparing to general population, patients with skin disorders suffer more often from depression and anxiety. Those two diseases are mentioned most frequently in the context of psychiatric side effect of drugs discussed in the article. SUMMARY: Psychiatric side effects of drugs used in dermatology are not common. However, given the rising incidence of mental health disorders worldwide, it is important to be aware of them.